Standard-Dose Atorvastatin Treatment in Patients With Symptomatic Middle Cerebral Artery Atherosclerotic Stenosis: A Vessel Wall Magnetic Resonance Imaging Study - Wu, Yejun; Li, Fangbing; Wang, Yilin; Hu, Tianxiang; Gao, Honghua (Frontiers in Neurology, 2021)
Background and purpose: Ischemic stroke can be caused by atherosclerotic lesions of the MCA. Some studies have shown the effects of statin treatment on carotid artery plaques, but little is known about the effects of statin treatment on MCA plaques. The purpose of this study was to validate the efficacy of standard-dose atorvastatin (20mg/day) in patients with symptomatic MCA atherosclerotic stenosis (SMAS) in northern China. Materials and Methods: This study is a prospective, single-arm, single-center, 12-month follow-up observational study monitoring imaging and clinical outcomes of standard-dose atorvastatin treatment among patients with SMAS. The primary outcomes were changes in vessel wall magnetic resonance imaging (VWMRI) and serum lipid profiles before and after (1, 3, 6, 12 months) statin treatment. Results: A total of 46 patients were recruited for this study, and 24 patients completed the follow-up. During the follow-up period, serum non-high-density lipoprotein cholesterol concentrations gradually decreased in the patients. 14 patients (54.33%) had a reversal of MCA plaques and 10 patients (41.67%) had no significant progression of MCA plaques and remained stable at the follow-up endpoint. Duration of 12 months did not reverse vascular remodeling, change the shape and distribution of plaques. Altered serum low-density lipoprotein cholesterol concentrations in patients were strongly associated with plaque reversal. Conclusion: VWMRI could accurately characterize changes in MCA plaques after lipid-lowering therapy. Standard-dose atorvastatin treatment could stabilize and reverse plaques in northern Chinese SMAS patients. Trial registration number: ChiCTR2000034235(http://www.chictr.org.cn/showproj.aspx?proj=55532).